Estimation of bovine leukemia virus (BLV) proviral load harbored by lymphocyte subpopulations in BLV-infected cattle at the subclinical stage of enzootic bovine leucosis using BLV-CoCoMo-qPCR - Panei, Carlos Javier (2013)
Background: Bovine leukemia virus (BLV) is associated with enzootic bovine leukosis (EBL), which is the most common neoplastic disease of cattle. BLV infection may remain clinically silent at the aleukemic (AL) stage, cause persistent lymphocytosis (PL), or, more rarely, B cell lymphoma. BLV has been identified in B cells, CD2+ T cells, CD3+ T cells, CD4+ T cells, CD8+ T cells, γ/δ T cells, monocytes, and granulocytes in infected cattle that do not have tumors, although the most consistently infected cell is the CD5+ B cell. The mechanism by which BLV causes uncontrolled CD5+ B cell proliferation is unknown. Recently, we developed a new quantitative real-time polymerase chain reaction (PCR) method, BLV-CoCoMo-qPCR, which enabled us to demonstrate that the proviral load correlates not only with BLV infection, as assessed by syncytium formation, but also with BLV disease progression. The present study reports the distribution of BLV provirus in peripheral blood mononuclear cell subpopulations isolated from BLV-infected cows at the subclinical stage of EBL as examined by cell sorting and BLV-CoCoMo-qPCR.Results: Phenotypic characterization of five BLV-infected but clinically normal cattle with a proviral load of > 100 copies per 1 × 105 cells identified a high percentage of CD5+ IgM+ cells (but not CD5- IgM+ B cells, CD4+ T cells, or CD8+T cells). These lymphocyte subpopulations were purified from three out of five cattle by cell sorting or using magnetic beads, and the BLV proviral load was estimated using BLV-CoCoMo-qPCR. The CD5+ IgM+ B cell population in all animals harbored a higher BLV proviral load than the other cell populations. The copy number of proviruses infecting CD5- IgM+ B cells, CD4+ cells, and CD8+ T cells (per 1 ml of blood) was 1/34 to 1/4, 1/22 to 1/3, and 1/31 to 1/3, respectively, compared with that in CD5+ IgM+ B cells. Moreover, the BLV provirus remained integrated into the genomic DNA of CD5+ IgM+ B cells, CD5- IgM+ B cells, CD4+ T cells, and CD8+ T cells, even in BLV-infected cattle with a proviral load of <100 copies per 105 cells.Conclusions: The results of the recent study showed that, although CD5+ IgM+ B cells were the main cell type targeted in BLV-infected but clinically normal cattle, CD5- IgM+ B cells, CD4+ cells, and CD8+ T cells were infected to a greater extent than previously thought.